2019
DOI: 10.1002/aenm.201901787
|View full text |Cite
|
Sign up to set email alerts
|

Rational Core–Shell Design of Open Air Low Temperature In Situ Processable CsPbI3 Quasi‐Nanocrystals for Stabilized p‐i‐n Solar Cells

Abstract: As a promising alternative, inorganic perovskite nanocrystals allow reinforced stability of photovoltaic device. Unfortunately, directly assembling these nanocrystals into film is uncontrollable. Instead, in situ assembling technology under low temperature in open air is attractive but limited due to the tendency of nonperovskite transition. The adverse shell ligands and unstable core lattices are known as the fundamental problems. In order to address this issue, here proposed is a rational core–shell design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…In our early work, we also believed that the HPbI 3 replaces PbI 2 leading to the formation of a stabilized distorted black phase . Most recently, Xi et al increased HI amount to fabricate another new compound H 2 PbI 4 to fabricate stabilized CsPbI 3 PSCs …”
Section: Tga Parameters Of Different Syn‐pbi2 Powders (Extracted Frommentioning
confidence: 93%
“…In our early work, we also believed that the HPbI 3 replaces PbI 2 leading to the formation of a stabilized distorted black phase . Most recently, Xi et al increased HI amount to fabricate another new compound H 2 PbI 4 to fabricate stabilized CsPbI 3 PSCs …”
Section: Tga Parameters Of Different Syn‐pbi2 Powders (Extracted Frommentioning
confidence: 93%
“…[13] Consequently,t he precursor of "HPbI 3 "a nd "HPbI x "h ave been developed to improve the deposition of black phase CsPbI 3 perovskite. [14,[20][21][22][23][24][25] Recently, some studies have revealed that the acid would react with the dimethylformamide (DMF) to form formic acid and dimethylamine (CH 3 ) 2 NH:DMA). [26,27] Therefore,the HI additive would induce the formation of DMAI, the previously reported "HI" additive and "HPbI 3 "s hould be DMAI and DMAPbI 3 .H ence,t he role of DMAI in the fabrication of CsPbI 3 should be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…[45] And most recently, Grätzel and coworkers also updated the PCE of 3D/2D organic-inorganic hybrid PSCs over 22% with water-and heat-resistant operationally stable. [49] 2) 2D structure: Jin and co-workers used long-chain ammonium as surface capping ligands resulting in the stabilized 2D structure based β-CsPbI 3 black phase. 1) 0D quantum dots (QDs): Reducing the crystal size will led to more surface to accommodate organic group, which makes the α-CsPbI 3 more stable.…”
mentioning
confidence: 99%